The effects of arts and crafts therapy on post-stroke executive dysfunction: a pilot randomized control test - Yun, Ruisheng; Zhou, Huanxia; Gray, Julie McLaughlin; Cheng, Jia; Zhao, Zhongzhi (Frontiers in Stroke, 2023)
Background: Executive function is an important determinant of independent living among stroke survivors. Patients with post-stroke executive dysfunction (PSED) have lower engagement in therapy activities and reduced independent living abilities. One potential method for improving executive function and engagement is arts and crafts therapy (ACT). This study aimed to explore the effects of ACT on PSED. Methods:The study was a pilot randomized controlled trial (RCT) with two groups: an experimental intervention group receiving ACT combined with individual rehabilitation therapy (IRT); and an active control group receiving IRT only. Fiftyseven (57) patients with PSED participated. Outcome measures included Trail Making Test (parts A and B), Stroop test, Tower of Hanoi (TOH) and Lawton-Brody IADL scale. Two groups were compared at baseline and four weeks after the completion of the training. Results: There were significant differences in TMT-A (time) (p<0.01), TMT-B (p<0.05), TMT-B (errors) (p<0.01) and Stroop test (time) (p<0.01) between the experimental and the control group after four weeks. There were no significant differences in TMT-A (errors), Stroop test (errors), TOH and IADL scale. Conclusion: Therapeutic use of arts and crafts could be an effective intervention to improve executive function and self-efficacy for stroke survivors.